1986
DOI: 10.1116/1.583535
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure studies of AuNiGe Ohmic contacts to n-type GaAs

Abstract: Transmission electron microscopy studies of the microstructure of AuNiGe ohmic contact to n-type GaAs Microstructure analysis and contact resistance measurements of alloyed AuNiGe contacts to GaAs were performed to assist in the development of low resistance Ohmic contacts for metalsemiconductor field-effect transistor (MESFET) devices. The contact metals were prepared by sequential deposition of 100 nm of Au-27 at. % Ge, 35 nm Ni, and 50 nm Au onto sputter-cleaned GaAs wafers in which conducting channels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(21 citation statements)
references
References 0 publications
1
18
0
2
Order By: Relevance
“…Although it has been fLrmly established that Ge in the Au-Ge-Ni system plays a crucial role in lowering Pc to very low values on GaAs [3,4], we have found that its presence is not necessary to achieve very low Pc values on InP. Our investigations of Ni, Au, Au-Ni, and Au-Ge-Ni contact systems on InP have resulted in several findings.…”
Section: Introductionmentioning
confidence: 69%
“…Although it has been fLrmly established that Ge in the Au-Ge-Ni system plays a crucial role in lowering Pc to very low values on GaAs [3,4], we have found that its presence is not necessary to achieve very low Pc values on InP. Our investigations of Ni, Au, Au-Ni, and Au-Ge-Ni contact systems on InP have resulted in several findings.…”
Section: Introductionmentioning
confidence: 69%
“…The surface oxide is known to increase effective Schottky barrier height and to deteriorate the metal/GaN interface, leading to the degradation of ohmic contacts. Historically, the Ni metallization was cited as a wetting agent [28], but it was later deduced that Ni has other roles including reduction of the surface oxides and reacting with GaN at low temperatures to form binary and ternary compounds that may be electrically important.…”
Section: Resultsmentioning
confidence: 99%
“…The surface oxide is known to increase effective Schottky barrier height and to deteriorate the metal/GaN interface, leading to the degradation of ohmic contacts. Historically, the Ir metallization was cited as a wetting agent [29], but it was later deduced that Ir has other roles including reduction of the surface oxides and reacting with GaN at low temperatures to form binary and ternary compounds that may be electrically important.…”
Section: Resultsmentioning
confidence: 99%